2022
DOI: 10.5005/jp-journals-10071-24001
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function, Reverse Triiodothyronine, and Mortality in Critically Ill Clinical Patients

Abstract: A bstract Background To evaluate the association of thyroid hormones changes, including increased reverse triiodothyronine (rT3) level, with critically ill clinical patients´ mortality. Patients and methods This study analyzed the observational data prospectively collected over 8 months (2018) in an adult intensive care unit (ICU) in Brasilia, Brazil. All consecutive ICU-admitted clinical patients were included. Thyroxine (T4), free thyroxine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Until recently, rT 3 has been identified as an inactive metabolite of thyroid hormone metabolism [ 200 ]. There have been reports indicating that rT 3 may produce unfavorable outcomes, including end-stage chronic kidney disease, acute myocardial infarction, hepatic diseases, and increased intensive care unit (ICU) mortality [ 201 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, rT 3 has been identified as an inactive metabolite of thyroid hormone metabolism [ 200 ]. There have been reports indicating that rT 3 may produce unfavorable outcomes, including end-stage chronic kidney disease, acute myocardial infarction, hepatic diseases, and increased intensive care unit (ICU) mortality [ 201 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that rT 3 levels are increased when there is food deprivation [ 38 , 105 , 155 ], and rT 3 may produce unfavorable clinical outcomes [ 201 ]. It is, however, unclear whether increased rT 3 levels during fasting or starvation are linked to unfavorable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism that could explain the isolated elevation of rT3 levels in D-1 is drop of its clearance in the liver that appears earlier, also leading to a fall in the FT3 levels. The low half-life of rT3 (around 3 h compared to 24 h for T3) makes rT3 a sensitive and earliest marker for acute changes in thyroid hormones' metabolism [32]. Similarly, Hosny et al 2015 found that only FT3 levels measured during follow up in day 5 was significantly decreased in nonsurvivors than survivors [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that all participants in the study had increased levels of rT3, which indicates its potential as a sensitive and early indicator for detecting acute alterations in thyroid hormone metabolism. The short half-life of rT3, approximately 3 h, further enhances its effectiveness in promptly identifying these changes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%